A imagem da escola pelos olhos dos futuros professores de arte - Franco, Katia Cilene de Mello (2006)
This paper is the result of a research that aimed to understand the school image an Arts group of students from different levels at a private university in São Paulo have. The social representation theory, the teacher background and Arts teaching will be the approach in this paper. They will help to establish the parameters for data analysis. A questionnaire combining writing and drawing was used to get the data. For people who answered it, the meanings of their participation at school are revealed in many metaphoric references, that are sometimes contradictory but raise the representation they have on the school sense. The observation of the data in this research showed, in general , that the school image built by the people involved is divided into two parts: first the idealized image, where learning and being happy have to be always present. And the other, where school is represented by the daily and common routine in the classroom, which is harder and even so, without losing the hope in changing